Analisis Pengaruh Konflik Kerja-Keluarga terhadap Kepuasan Kerja Pengusaha Wanita di Kota Semarang - Susanto Susanto (STIE Widya Manggala, 2010)
The purpose of this research was to investigate the effect of job-spouse conflict, job-parents conflict and job-homemaker conflict on job satisfaction. Using these variables, for instance Lee dan Choo (2001), Agung Harsiwi (2004), Afina Murtiningrum (2005), discovered effect job-spouse conflict, job-parents conflict and of job-homemaker conflict toward job satisfaction. Methodology research as the sample used purposive sampling. The samples were 43 women entrepreneurs in Semarang. The data analysis was multiple linear regressionsof ordinary least square and hypotheses test used t-statistic and F- statictis at level of significance 5%, a classic assumption examination was also done to test the hypotheses. During research period showing as variable and data research were normal distributed. Basedon the test, multicolinearity test and heterokedasticity test classic assumption deviation had no founded, this indicated that the available data had fulfilled the condition to use multiple linear regression model. This result of research showed that variable job-spouse conflict waspositively related on job satisfaction, job-parents conflict was not related on job satisfaction and job-homemaker conflict was not related on job satisfaction. Prediction capability from these three variables toward job satisfaction was 23,9 %, where the balance 76,1%, was affectedto other factor which was not to be entered to research model.